Adherence of patients with type 2 diabetes mellitus with the SEMDSA lifestyle guidelines. Issue 2 (31st July 2018) - Birkinshaw, Amy; Nel, Riette; Walsh, Corinna
Abstract : Background: Type 2 diabetes mellitus (T2DM) is considered to be the fastest growing chronic disease in the world and thus multi-sectoral, population-based strategies and approaches are needed to address the modifiable risk factors involved in the development and treatment of T2DM. Evidence-based nutrition principles and recommendations are summarised by the Society for Endocrinology, Metabolism and Diabetes in South Africa (SEMDSA) into guidelines for the management of T2DM. This study aimed to determine the adherence of patients with T2DM with the SEMDSA lifestyle guidelines. Methods: A cross-sectional study was conducted in a private practice ( n = 50), during which an interviewer-assisted questionnaire related to socio-demographics, diet and lifestyle was completed with each participant. Participants were also weighed and measured. Results: 88% of participants were overweight (22%) or obese (66%). Diets consumed were generally high in total energy (TE) (median: 13 272 kJ), low in carbohydrates (CHO) (56% of participants consumed < 45% of CHO from TE), high in saturated fat (92% consumed ≥ 7% from TE) and high in sodium (74% of participants consumed ≥ 2 300 mg sodium daily). Exercise was not commonplace; 84% of participants did not meet the guideline for aerobic exercise and 92% did not meet the guideline for resistance training. Conclusion: The adherence of participants to the SEMDSA guidelines was poor, thus increasing the risk of long-term complications and poor glycaemic control.